2007
DOI: 10.2343/geochemj.41.47
|View full text |Cite
|
Sign up to set email alerts
|

Mesozoic monazite in Neoproterozoic metasediments: Evidence for low-grade metamorphism of Sinian sediments during Triassic continental collision, Liaodong Peninsula, NE China

Abstract: Sericite phyllite from the Sinian Shisanlitai Formation, Dalian area, Liaodong Peninsula, NE China, contains an assemblage of newly-formed lower-greenschist facies minerals (sericite, chlorite, Fe minerals and Ti minerals) plus aggregates of fine-grained monazite. The texture of the monazite, its mineral inclusions, and its close association with Fe oxide minerals show that it is not detrital or diagenetic, but a product of the low-grade metamorphism. SHRIMP U-Th-Pb dating of the monazite at 217 ± 15 Ma shows … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…In recent years, lots of scholars focus on the chronology method of magmatic rocks to constrain the subduction time (Liu et al, 2017; Tang et al, 2018; W. L. Xu et al, 2012), but it still remains controversial. With the detrital zircons LA‐ICP‐MS U–Pb dating technology gradually growing mature in China and abroad, studying detrital zircons U–Pb ages of sediments can help geologists search for sediments source areas and discuss tectonic evolution of study area accurately and quickly (Dickinson & Gehrels, 2008; Gehrels, 2014; Tang, Zheng, Wu, & Gong, 2006; Wan et al, 2007). At the same time, detrital zircons U–Pb age spectra in sediments comprise extensive age information, so studying detrital zircons U–Pb dating of sedimentary rocks also can highlight orogenic evolution, magmatic activity, continental formation and elucidate the tectonic background of the basin, including the period of formation (Cawood, Hawkesworth, & Dhuime, 2012; Hu, Cawood, Du, Yang, & Jiao, 2015; Z. J. Xu, Lan, Kong, Cheng, & Wang, 2018; X.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, lots of scholars focus on the chronology method of magmatic rocks to constrain the subduction time (Liu et al, 2017; Tang et al, 2018; W. L. Xu et al, 2012), but it still remains controversial. With the detrital zircons LA‐ICP‐MS U–Pb dating technology gradually growing mature in China and abroad, studying detrital zircons U–Pb ages of sediments can help geologists search for sediments source areas and discuss tectonic evolution of study area accurately and quickly (Dickinson & Gehrels, 2008; Gehrels, 2014; Tang, Zheng, Wu, & Gong, 2006; Wan et al, 2007). At the same time, detrital zircons U–Pb age spectra in sediments comprise extensive age information, so studying detrital zircons U–Pb dating of sedimentary rocks also can highlight orogenic evolution, magmatic activity, continental formation and elucidate the tectonic background of the basin, including the period of formation (Cawood, Hawkesworth, & Dhuime, 2012; Hu, Cawood, Du, Yang, & Jiao, 2015; Z. J. Xu, Lan, Kong, Cheng, & Wang, 2018; X.…”
Section: Introductionmentioning
confidence: 99%
“…Read et al 1987;Rasmussen et al 2001Evans et al 2002;, 2009Wan et al 2007;Wilby et al 2007), all the more, as the bulk has relatively high Th and Y contents (Appendix). Bearing in mind the age dating and temperatures recorded on illite fractions presented in Biševac et al (2009Biševac et al ( , 2010, we can assume that the population of Th-and Y-monazites found in sample R15 are Alpine (Cretaceous).…”
Section: Sources Of Metasedimentary Rocksmentioning
confidence: 99%
“…As the direct recorder of important events such as massif collision and basin‐mountain coupling, the Early Permian Erlongshan Formation clastic rocks in Mishan provide us with an important research carrier to clarify the source characteristics of sediments at the boundary of the two massifs, and then reveal the assembly relationship between the Early Permian Jiamusi Massif and the Khanka Massif. With the gradual maturity of detrital zircon U–Pb dating technology and the increasingly extensive information contained in it in recent years (Dickinson & Gehrels, 2008; Gehrels, 2014; Tang et al, 2006; Wan et al, 2007), we can compare the detrital zircon U–Pb dating data of sedimentary rocks with the ages of strata (bodies) in potential source areas around the study area (Fedo, 2003; Yao et al, 2017; Zhang et al, 2018). It provides a new and effective method for provenance analysis.…”
Section: Introductionmentioning
confidence: 99%